The Service Quality Effect Towards the Customer Satisfaction of Bank in Indonesia - Bakhtiar Tijjang; Nurfadhilah Nurfadhilah; Pandi Putra (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
Nowadays the competition of the company is started increasingly and tighter. The success factor is strongly determined by the level of customer satisfaction. Satisfied customers are needed very much by the company. Customer satisfaction can only be achieved by providing quality services to consumers. The purpose of this study is to examine and analyze the impact of service quality which consists of five variables, which are physical evidence, reliability, responsiveness, assurance, and empathy on customer satisfaction at PT Bank Mandiri (Persero) Tbk. Parepare Branch. The data were collected by providing questionnaires to 100 customers who were sampled in this study. The samples were selected using proportionate stratified random sampling method. The collected data were analyzed using multiple linear regression analysis that supported of SPSS version 21 application. The results of the analysis show that partially, there is no one variable of service quality that has no effect on customer satisfaction, the variable is physical evidence, while the other variables have a positive and significant effect on customer satisfaction. Otherwise, if the determined results simultaneously are the five variables of service quality that both have a positive and significant effect on customer satisfaction.